2020
DOI: 10.1111/jcmm.15747
|View full text |Cite
|
Sign up to set email alerts
|

CircPSMC3 alleviates the symptoms of PCOS by sponging miR‐296‐3p and regulating PTEN expression

Abstract: Polycystic ovary syndrome (PCOS), the most common female endocrine disease that causes anovulatory infertility, still lacks promising strategy for the accurate diagnosis and effective therapeutics of PCOS attributed to its unclear aetiology. In this study, we determined the abnormal reduction in circPSMC3 expression by comparing the ovarian tissue samples of PCOS patients and normal individuals. The symptom relief caused by up‐regulation of circPSMC3 in PCOS model mice suggested the potential for further study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Increasing evidence has demonstrated that PTEN acts as a tumor suppressor functionally involved in many types of cancers, including HCC. 53 , 54 , 55 Interestingly, we verified similar results in this study through survival analysis, IHC, and copy number variation analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Increasing evidence has demonstrated that PTEN acts as a tumor suppressor functionally involved in many types of cancers, including HCC. 53 , 54 , 55 Interestingly, we verified similar results in this study through survival analysis, IHC, and copy number variation analysis.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that circRNAs are collectively involved in the initiation and development of PCOS. For example, circPSMC3 suppresses granulosa tumor cell proliferation and facilitates their apoptosis in PCOS [ 18 ]. Additionally, downregulation of circPUM1 enhances proliferation and inhibits apoptosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs collectively participate in the initiation and development of endocrine dyscrasia in females. For instance, dysregulated circRNAs are associated with the progression of gestational diabetes mellitus, cardiovascular diseases, obesity, and PCOS [9][10][11][12]. Overexpressed circRNA_0054633 contributes to gestational diabetes mellitus and the increase of glycosylation index [27].…”
Section: Discussionmentioning
confidence: 99%
“…This confer its stability in various biological functions, such as post-transcription, RNA-related protein binding, gene splicing, and modi cation of parental gene expression [7,8]. However, dysfunction of circRNAs is evidenced to be associated with endocrinopathy, such as type 2 diabetes mellitus, cardiovascular diseases, obesity, and PCOS [9][10][11][12]. For instance, knockdown of circRNA_DMNT3B contributes to diabetic nephropathy via regulating miR-20b-5p/BAMBI [13].…”
Section: Introductionmentioning
confidence: 99%